Comparison of Measurements for Recording Postural Control in Standing and Seated Position in Healthy Individuals - Philipp Floessel; Franziska Hammerschmidt; Jan Jens Koltermann; Justin Foerster; Heidrun Beck; Alexander Carl Disch; Thomas Datzmann (Journal of Functional Morphology and Kinesiology)
Background: A standard method of assessing postural control is to measure while standing. However, its implementation is usually limited. Recording postural control directly on the trunk in a seated position could provide an alternative diagnostic method for quantifying neuromuscular control. Methods: A comparison of center of pressure (CoP) measurements in the standing and sitting positions was performed on 66 healthy adult subjects. The reliability of the measurements in the sitting position was tested in 23 subjects. In addition, the extension force of all test subjects was recorded. Results: The assessments of CoP fluctuations in standing and seated positions showed adequate agreement (deviation 9.1%). Furthermore, good internal consistencies with a sufficient test–retest reliability could be demonstrated for the measurements in seated position. Both CoP measurement methods showed a comparable Spearman correlation to obtained extension force measurements (standing: 0.24, seated: 0.23). Conclusions: Our results show that recording CoP fluctuations in the sitting position is a reliable and valid adjunct to single-leg stance measurements. It could serve as an additional alternative to quantify neuromuscular control in impaired patients who cannot adequately perform the single-leg stance. In addition, measurement in the seated position allows direct recording of neuromuscular control at the trunk.